The Role of Perceived Sports Competence and Sport Anxiety in Determining Self-Talk in Elite Athletes (Journal of Pharmaceutical Negative Results, 2022)
The purpose of our research was to investigate the role of sport anxiety and perceived sports competence in determining the utilization of self-talk in elite athletes. Fifty six female (X̅age=24.62±3.40) and 65 male (X̅age=24.50±6.50); a total of 121 (X̅age=24.56±5.28) athletes who have at least three years of competitive experience and have previously represented Turkey with the national athlete title at international sports competitions were voluntarily participated in the study. Participants were given a personal information form along with the sports competence subscale of the physical self-description questionnaire which was developed by Marsh Richards, Johnson, Roche and Tremayne (1994) and adapted into Turkish by Marsh, Asci and Marco in 2002; the sport anxiety scale which was developed by Smith, Smoll, Cumming and Grossbard (2006) and adapted into Turkish by Akyol, Altintas, Sezer and Asci in 2016; the self-talk questionnaire which was developed by Zervas, Stavrou and Psychountaki (2007) for the purpose of determining athletes’ self-talk forms and was adapted into Turkish by Engur in 2011. After exploring a normally distributed data, the hierarchical regression analysis was used to determine the role of sports competence and sports anxiety in predicting the athletes' self-talk types. As a result of the research, statistically significant differences in both sports competence and self-talk usage levels were found between groups according to sport type and a statistically significant relationship was found in predicting motivational self-talk for both competition experience and sport type.